Software Effort Estimation Techniques - kumar, Neeraj; kumar, Yogesh; Rishi, Rahul (International Journal of Computer Sciences and Engineering, 2019)
One of the major concern of every software organization is software effort estimation. As size and complexity of software increases, it becomes very difficult to estimate the cost of efforts needed to built the software. This has attracted many researchers. Software estimation techniques applied by some of them gave good results and some did the opposite but none of the techniques has given accurate results in every situation. This paper focuses on literature review on research studies done in this field in the past few years. Comparative analysis of those techniques is also done.